The Influence of Service Quality and Price on Consumer Satisfaction at Top Swalayan Kolaka - Niar Astaginy; Sudarnice Sudarnice; Kasmawati Kasmawati (MAMEN: Jurnal Manajemen, 2023)
The purpose of this study was to determine the effect of service quality and price on consumer satisfaction at Top Swalayan Kolaka. This research is survey research using a questionnaire as an instrument. The population in this study were all consumers at the Top Swalayan Kolaka and taken as many as 90 respondents using accidental sampling, namely anyone who coincidentally met a researcher who was known to have used the product of Top Swalayan Kolaka. Data collection techniques are primary data and secondary data. The data obtained were analyzed using PLS analysis techniques through SmartPLS software. The results showed that service quality had a positive and significant effect on customer satisfaction. This is evidenced by the t-count or t-statistic which is 6.288 higher than the t-table value of 1.662 and the price also has a positive and significant effect on consumer satisfaction because the t-count or t-statistic value is 7.450 higher than the t-table value. which is 1,662. The service quality and price variables have a positive and significant impact on customer satisfaction of 74.2%.